DTHB3D_Reg: Dynamic Truncated Hierarchical B-Spline Based 3D Nonrigid Image Registration (Communications in Computational Physics, 2018)
We present a robust approach to perform 3D nonrigid image registrationsuitable for large deformation and topology change, and develop a software packagenamed DTHB3D Reg (Dynamic Truncated Hierarchical B-spline based 3D ImageRegistration). The optimum spatial transformation, defined using truncated hierarchicalB-splines, is obtained through the minimization of an energy functional. Theoptimization process minimizes sum of squared difference in the intensity values ofthe grayscale images. Control points are dynamically updated without constructinglarge matrices as in finite element method. To improve the computational efficiency,an adaptive strategy carries out refinement only in the regions with large deformation.The proposed method is demonstrated on 3D synthetic and medical images to showrobustness on topology change as compared to other image registration methods.
Keywords: 3D nonrigid image registration; dynamic scheme; truncated hierarchical B-spline; adaptive refinement; topology change.